2000
DOI: 10.1029/2000jb900117
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical characteristics of the southern Mariana Trough, 11°50′N–13°40′N

Abstract: Abstract. Despite slow opening rates generally inferred for the Mariana Trough, the southernmost part of the basin has "fast spreading" geophysical and morphologic characteristics that are unlike the features of the basin to the north. A side-scan sonar and geophysical survey maps the eastern part of the basin and the seafloor spreading center between 11 ø50'N and 13ø40'N and identifies the following characteristics: the ridge across-axis profile forms a triangular to rounded high with relief of 100 to 500 m a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(168 citation statements)
references
References 74 publications
8
158
1
1
Order By: Relevance
“…They also argue that the lack of sediments covering the deformed ocean floor further indicates that the accelerated extension and southward migration of the Mariana Trench in this region has occurred recently. One may argue that extensional faulting of forearcs alone is not enough to prove slab rollback, because normal faulting may also be caused by basal subduction erosion, but we still favor the rollback interpretation based on two additional lines of evidence: the shallow asthenosphere penetration between the two plates (this study) and the opening rate of the Mariana Trough back arc basin that increases southward Kato et al, 2003;Martinez et al, 2000]. These three processes are all explained by rapid rollback of the subducting slab.…”
Section: Plate Coupling and Slab Dynamicsmentioning
confidence: 81%
See 2 more Smart Citations
“…They also argue that the lack of sediments covering the deformed ocean floor further indicates that the accelerated extension and southward migration of the Mariana Trench in this region has occurred recently. One may argue that extensional faulting of forearcs alone is not enough to prove slab rollback, because normal faulting may also be caused by basal subduction erosion, but we still favor the rollback interpretation based on two additional lines of evidence: the shallow asthenosphere penetration between the two plates (this study) and the opening rate of the Mariana Trough back arc basin that increases southward Kato et al, 2003;Martinez et al, 2000]. These three processes are all explained by rapid rollback of the subducting slab.…”
Section: Plate Coupling and Slab Dynamicsmentioning
confidence: 81%
“…At that point, the forearc narrows to only $50 km, and the distance from the actively spreading Mariana Trough back arc basin, which must be underlain by shallow asthenosphere, to the trench narrows to $100 km. In between, a dispersed group of seamounts (at about 142.5°E 11.8°N, Figure 1a) appear to be the southward continuation of the magmatic arc [Fryer, 1996;Fryer et al, 1998;Martinez et al, 2000]. The crust of this newly developing magmatic arc may not have thickened a lot, but even if the crust is 10-km thick, the depth of about 2.0 km below sea level indicates that here too, only 50 km away from the trench, the asthenosphere is very shallow.…”
Section: Shape Of the Asthenospheric Wedge Between Subducting And Ovementioning
confidence: 99%
See 1 more Smart Citation
“…The proximity, as well as the radial faulting pattern of the eastern backarc basin south of 13 10 0 N, may facilitate channeling of arc magma to the spreading center (Fryer 1995;Fryer et al 1998). Martinez et al (2000) proposed that the welldeveloped spreading system, in contrast to the rifting-stage system of the Northern Mariana Trough, channels arc magma efficiently along the backarc-spreading axis. They also suggested that the small arc seamounts in the Southern Mariana Trough may also support the derivation of the arc magmatic budget to the spreading center.…”
Section: Source Of a Range In Sulfur Isotopic Compositions For Sulfidmentioning
confidence: 99%
“…It is located between the southern terminus of the Mariana Trough back-arc spreading center, called the Malaguana-Gadao Ridge (referred to as the Southern Mariana Trough by Brounce et al [2014]), and the Southeastern Mariana Forearc Rift, an unusual region of forearc extension and related volcanism [Fryer, 1995;Ribeiro et al, 2013b]. The southernmost Marianas, between the Malaguana-Gadao Ridge in the west, the Mariana trench in the east and the south, and the Alphabet seamount volcanic province in the north, is a tectonically complex and rapidly deforming region [Fryer, 1995;Kato, 2003;Martınez et al, 2000]. The upper plate is extending southeast-northwest, accommodated by spreading along the Malaguana-Gadao Ridge.…”
Section: Geologic Backgroundmentioning
confidence: 99%